A conceptual frame work for digital marketers in the young parisian target (25-29 years old) - Lizana Castro, Miguel Angel (Universidad ESAN, 2019)
Digital marketing is evolving day to day and the digital channel is becoming the mainstream interaction space between sellers and potential buyers in a B2C context. Digital marketing, like any other conventional mode of marketing, is intended to interact with consumers and make them commit to what the marketer proposes; influence them and turning them into buyers. Wherever the consumer interacts, there arises the significance of behavioral studies, as the marketer has to align his marketing strategies to interact better with the consumer. The study I am proposing here is aimed to understandand answer the following question: What motivates the consumer to purchase a product or service online? Thereby framing a conceptual model where one can assess the interaction between digital marketing and consumer by different contact dots, and overlapping these dots in order to understand the vice versa flow in the interactions. For that, this paper streams through the various literature that mentions several digital marketing parameters with the key concepts in consumer behavior and motivations. I conducted a survey to Parisians into the age range of 25 to 29, this survey was made with the questions twinning the concepts of digital marketing and consumer motivation, elaborating the hypothesis in accordance with the theory which I had derived out of the literature. That theory functions as the conceptual model that I had proposed and matching with the results of the survey to end with the most influence drivers and ranking them in order to present to digital marketers where they could allocate their resources to have a better rate of conversion and be more efficiency. I had identified the internal and external consumer motivators (derived from the theory) and was able to demine which consumer motivational factors affect the marketer's return in accordance with the purchase decision of the consumer. This conceptual framework that I propose could be used for further studies focusing on more on consumer motivations with other determinants of digital marketing. In addition, this conceptual model could be used in other geographical areas, with another range of ages. For instance, in Peru that currently there is a tendency for B2C companies to migrate to multichannel and omnichannel models, this conceptual framework could be used to understand better the consumer motivations (extrinsic and intrinsic), framing to the target public that the companies would have. It is recommendable to marketers frame and structure the customer portrait with 2 big factors: Demographic and geographic, with those it would be possible apply this conceptual framework and use the variables to conduct the surveys.
Keywords: Marketing digital; Comercio electrónico; Consumidores jóvenes; Comportamiento del consumidor; Motivación; https://purl.org/pe-repo/ocde/ford#5.02.04